2018
DOI: 10.1128/jb.00676-17
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium diphtheriae Iron-Regulated Surface Protein HbpA Is Involved in the Utilization of the Hemoglobin-Haptoglobin Complex as an Iron Source

Abstract: utilizes various heme-containing proteins, including hemoglobin (Hb) and the hemoglobin-haptoglobin complex (Hb-Hp), as iron sources during growth in iron-depleted environments. The ability to utilize Hb-Hp as an iron source requires the surface anchored proteins HtaA and either ChtA or ChtC. The ability to bind hemin, Hb and Hb-Hp by each of these proteins requires the previously characterized Conserved Region (CR) domain. In this study, we identified an Hb-Hp binding protein, HbpA (38.5-kDa), which is involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 71 publications
(110 reference statements)
0
7
1
Order By: Relevance
“…Indeed, HbpA deletion mutants in iron depleted media showed reduced ability to use the Hb:Hp complex as an iron source, while showing no difference in the use of Hb or haem. [37] In summary, HtaA, HtaB, ChtA and ChtC are surface exposed proteins of C. diphtheriae and are able to bind host haemoproteins, starting the cascade of haem-passing interactions that follow; for example, HtaA to HtaB to HmuT then onto HmuUV for transmembrane transportation. The ability to use Hb as an iron source is not unique within the genus to C. diphtheriae.…”
Section: Corynebacterium Diphtheriaementioning
confidence: 99%
“…Indeed, HbpA deletion mutants in iron depleted media showed reduced ability to use the Hb:Hp complex as an iron source, while showing no difference in the use of Hb or haem. [37] In summary, HtaA, HtaB, ChtA and ChtC are surface exposed proteins of C. diphtheriae and are able to bind host haemoproteins, starting the cascade of haem-passing interactions that follow; for example, HtaA to HtaB to HmuT then onto HmuUV for transmembrane transportation. The ability to use Hb as an iron source is not unique within the genus to C. diphtheriae.…”
Section: Corynebacterium Diphtheriaementioning
confidence: 99%
“…In addition to the heme-binding proteins mentioned above, a unique iron-regulated, Hb- and Hb-Hp binding protein (HbpA) was also identified in C. diphtheriae [ 40 ]. HbpA is both located in the membrane and secreted, and exists in a large-molecular-weight aggregate that is important for optimal binding to Hb and Hb-Hp [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…HbpA is both located in the membrane and secreted, and exists in a large-molecular-weight aggregate that is important for optimal binding to Hb and Hb-Hp [ 41 ]. HbpA does not bind heme and contains a CR domain but can bind Hb and Hb-Hp [ 40 ]. Structural analysis of HbpA protein revealed that the C-terminal region is pivotal for the use of heme-iron from Hb-Hp and plays a role in anchoring to the membrane [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations